Experimental clinical substantiation of application of immobilized forms of sodium hypochlorite in treatment of infected pancreatonecrosis - B. S. Sukovatykh; V. A. Zhukovskiy; Yu. Yu. Blinkov; A. I. Itinson; E. A. Elenskaya; V. M. Pashkov (Вестник хирургии имени И.И. Грекова, 2017)
OBJECTIVE. The study substantiated the possibility of application of sodium hypochlorite for treatment of infected pancreatonecrosis. MATERIAL AND METHODS. The experimental study was conducted on 288 rats. Clinical research was carried out on 94 patients who were divided into two statistically homogenous groups. «Levomecol» ointment was used in the first group for sanation of omental bursae (lesser sac). The immobilized form of sodium hypochlorite was applied for the second group. RESULTS. Anti-inflammatory activity of immobilized form of sodium hypochlorite exceeded this activity in case of «Levomecol» application in 1,2-1,4 times. Anti-microbial activity was higher in 1,6-1,8 times at different terms of treatment of experimental animals. The proposed method of treatment of infected pancreatonecrosis allowed doctors to decrease the number of postoperative complications in patients on 11,2 % and lethality - on 9,2 %. CONCLUSIONS. It was stated that the application of immobilized forms of sodium hypochlorite for sanation of the omental bursae was pathogenically justified and efficient.